2022
DOI: 10.1093/ckj/sfac181
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models for predicting acute kidney injury: a systematic review and critical appraisal

Abstract: Background The number of studies applying machine learning (ML) to predict acute kidney injury (AKI) has grown steadily over the last decade. We assess and critically appraise the state of the art in ML models for AKI prediction considering performance, methodological soundness, and applicability. Methods We searched PubMed and ArXiv, extracted data, and critically appraised studies based on the TRIPOD, CHARMS, and PROBAST gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…39 The DDA involves using statistical and computational techniques to obtain meaningful patterns and insights from complex datasets and using these ndings to inform the selection of appropriate ML algorithms, features, and hyperparameters. Although the MDA in uenced the ML development methodologies of most studies related to the prediction of AKI, 17,18 a combination of both architectures guided the project design and development of this study. The input features were identi ed based on literature review and consultation with kidney experts in our research team to guide the model developments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 The DDA involves using statistical and computational techniques to obtain meaningful patterns and insights from complex datasets and using these ndings to inform the selection of appropriate ML algorithms, features, and hyperparameters. Although the MDA in uenced the ML development methodologies of most studies related to the prediction of AKI, 17,18 a combination of both architectures guided the project design and development of this study. The input features were identi ed based on literature review and consultation with kidney experts in our research team to guide the model developments.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,16 The estimation of baseline sCr has been especially important in studies developing and validating machine learning (ML) models to predict AKI. 17,18 In general, these studies have used different methods of estimating the baseline sCr to establish the ground truth in order to label positive AKI occurrences. This can lead to discrepancies in how AKI events are identi ed and labelled, making direct comparisons of the models' performance metrics challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrequent external validation of ML models for the prediction of acute events in the ICU was already noted in a 2019 systematic review, with only 7% of studies at the time using geographically independent data for model validation [8]. This has been echoed in more recent, disease-specific reviews looking at models for sepsis [20] and acute kidney injury [42]. While we showed that this percentage has somewhat improved since, we also find that challenges remain even if external validation is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Both AKI and sepsis are also highly heterogeneous [21]. This makes models built with conventional FL strategies such as federated averaging challenging to generalize across clinics, limiting their use [7,22,23]. Several federated architectures have been proposed to mitigate effects of data heterogeneity in other domains and built personalized, but globally correlated, models to mitigate drift across sites [23], such as model-agnostic meta-learning (MAML), federated multitask learning, and knowledge distillation [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%